Studi Potensi Obyek Daya Tarik Wisata Alam dan Strategi Pengembangan Pariwisata TWA Danau Dendam Tak Sudah Kota Bengkulu - Dian Nata Yasrij; Wiryono Wiryono; Yansen Yansen; Gunggung Senoaji; Yurike Yurike (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2026)
This research aims to determine the potential of natural tourist objects and attractions in the Lake Dendam Tak Sudah Natural Tourism Park (TWA), examine the Analysis of the Operational Area for Natural Tourist Attraction Objects (ADO-ODTWA) whether they are suitable for development, examine the characteristics and opinions of visitors regarding tourism development in the Lake Dendam Tak Sudah TWA, examine the characteristics and opinions of the community regarding tourism development in the Lake Dendam Tak Sudah TWA and formulate recommendations for tourism development strategies in the Lake Dendam Tak Sudah TWA. The research method uses the Regional Analysis of Operational Areas of Natural Tourist Attractions and Attractions (ADO – ODTWA) from the Directorate General of PHKA, Department of Forestry in 2003 to assess the potential of natural tourist attraction objects, descriptive analysis with a quantitative approach for the characteristics and opinions of the community and visitors and uses SWOT analysis for strategy development. The results of the research into the potential natural tourism attraction objects of TWA Lake Dendam Tak Sudah Jadi have a combination of natural beauty, unique ecosystem and cultural values ​​of the surrounding community, including Lake Dendam Tak Sudah itself, swamp forests and endemic vegetation, docks and boat tours as well as local culture. The results of the research also show that the TWA DDTS area is very suitable for development because it has an average feasibility index of 96.80%, with 9 criteria that are feasible and only 4 criteria that are not feasible, namely accommodation, visitor facilities and infrastructure, visitor management and marketing. Most of the visitors are not married because they are mostly teenagers. The majority of visitors' opinions about tourist attractions at TWA DDTS agree that they should be developed. The people of Dusun Besar Subdistrict are dominated by the productive age group, the education level of most of them is high school graduates with the majority of their livelihoods being traders. Most of the community is very supportive of tourism development in the TWA DDTS tourist area. The strategy for developing the TWA Air Hitam tourist attraction is at coordinates (1.413 ; 0.742) in quadrant I which has an aggressive strategy, namely 1) Development of ecotourism based on conservation and local wisdom 2) Empowerment of productive communities as drivers of natural tourism 3) Improvement of infrastructure and supporting facilities for natural tourism 4) Multi-stakeholder collaboration in developing sustainable tourism areas 5) Strengthening the image and promotion of natural tourism in Bengkulu Province